2006
DOI: 10.1007/s10803-006-0324-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperserotonemia in Adults with Autistic Disorder

Abstract: Hyperserotonemia is the most consistent serotonin-related finding in autism. The basis of this phenomenon, and its relationship to the central serotonergic dysfunction remains unclear. Platelet serotonin level (PSL) in 53 autistic adults and 45 healthy controls was measured. Mean PSL in autistic group (75.7 +/- 37.4 ng/microL) was significantly higher than the control sample (59.2 +/- 16.2 ng/microL) due to a presence of hyperserotonemic subjects which comprised 32% of the patients. PSL of autistic subjects di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 28 publications
4
67
0
Order By: Relevance
“…An early study in 1961 showed an increased levels of endogenous 5-HT in whole blood in 26% of autistic children [19]. These results have also been confirmed by other studies [20].…”
Section: Discussionsupporting
confidence: 62%
“…An early study in 1961 showed an increased levels of endogenous 5-HT in whole blood in 26% of autistic children [19]. These results have also been confirmed by other studies [20].…”
Section: Discussionsupporting
confidence: 62%
“…Evidence suggests that there is a large amount of genetic, phenotypic, and clinical heterogeneity among individuals with ASD. For example, preliminary evidence suggests that about 30% of people with ASD might have hyperserotonaemia 133 and thus are likely to respond well to drugs that modulate the serotonergic system, whereas about 70% do not, which could also explain the low treatment response to serotonergic drugs in large-scale clinical trials. Thus, ASD probably cannot be treated with a one-size-fi ts-all approach; treatment needs to be more personalised and individually tailored.…”
Section: Diagnostic Methods For Asd and Their Limitationsmentioning
confidence: 99%
“…The first one was the immediate 5HT precursor, which elevated 5HT levels without acting that genes which regulate 5HT metabolism should be considered as potential candidates in 5HT-related behavioral disorders. Indeed, our findings in autistic subjects indicated that disrupted 5HT homeostasis is related to alterations in 5HT metabolism rather than 5HT uptake [45,46]. Second, the developmental disbalance induced in both 5HT-compartments …”
Section: The Effects Of Pharmacological Treatments On the Expression mentioning
confidence: 64%